Analisis ‘Urf terhadap Adat Kincai Kawai Seanok di Desa Koto Tuo Pulau Tengah Kabupaten Kerinci, Jambi - Muhammad Imron; Azwani Lubis (CV Global Research Publication, 2026)
This study examines the practice of Kincai Kawai Seanok customary marriage in Koto Tuo Pulau Tengah Village, Kerinci Regency, as a traditional marital system that continues to be practiced across generations. This custom regulates marriages between couples who share certain kinship ties, with a primary requirement known as “cross lineage,” meaning that the parents of both parties must be related through different genealogical lines (e.g., paternal and maternal lines). The objective of this study is to analyze the practice of this custom and evaluate its compatibility with Islamic law through the perspective of ʿurf (customary practice). This research employs a qualitative approach with an empirical method. Primary data were collected through direct interviews with traditional leaders and local community members, while secondary data were obtained from books and scholarly articles related to marriage and Islamic law. The analysis uses the concept of ʿurf to determine whether the custom falls under ʿurf ṣaḥīḥ (valid custom) or ʿurf fāsid (invalid custom). The findings reveal that the Kincai Kawai Seanok custom requires a cross-lineage marriage pattern and prohibits certain types of marriages that are actually permissible in Islamic law, such as cousin marriage. This prohibition is based on customary rules that contradict Islamic provisions regarding mahram. From the perspective of ʿurf, this practice is categorized as ʿurf fāsid because it conflicts with Islamic legal principles, which allow cousin marriage. Therefore, a re-evaluation of this customary practice is necessary to ensure alignment with Islamic values while preserving local cultural identity.